Political economy, capitalism, and popular culture - Lipschutz, Ronnie D. (Rowman & Littlefield Publishers, 2010)
"This entertaining and enlightening book provides a guide to basic concepts and practices in capitalism, neoclassical economics, and political economy through an interpretation of popular films and novels of the past sixty years. Including works as varied as The Matrix, Lord of the Flies, The Dark Knight, Fight Club, and The Return of Martin Guerre, Ronnie Lipschutz describes and analyzes their essential role in the production and reproduction of contemporary society. His thoughtful and imaginative critique will bring to life the concepts and practices of economics and political economy for all readers."--Pub. desc